2006
DOI: 10.1007/s00216-005-0228-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a proteomics approach to identify favourable conditions for production of good quality lambskin leather

Abstract: It is necessary to understand the changes that occur during the initial processing of lamb skins, because these will affect the final quality of the leather. The types of collagen, their macro and micro structures, the presence of proteins other than collagens, and the quantity and the type of proteoglycans, all have a profound effect on the quality of leather. Proteins isolated from untreated or raw sheep skin and from pickled skin (skins treated with sodium sulfide and lime followed by bating with enzymes, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In particular, the processes of unhairing, liming/deliming, bating and picking have been optimized in order to remove cells, hairs, non-collagenous proteins and fats, yet they have to preserve the native fibrillar architecture of the animal skin. Proteomics studies performed on lambskin, analogous to the skin we used in this article, reported that pickled skins are almost entirely constituted by fibrillar collagen with a low percentage of elastin (~3% in weight) and traces of decorin (Choudhury et al, 2006). Washing with PBS removes inorganic salts that are normally present in pickled skin, which might be harmful for cell cultures.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the processes of unhairing, liming/deliming, bating and picking have been optimized in order to remove cells, hairs, non-collagenous proteins and fats, yet they have to preserve the native fibrillar architecture of the animal skin. Proteomics studies performed on lambskin, analogous to the skin we used in this article, reported that pickled skins are almost entirely constituted by fibrillar collagen with a low percentage of elastin (~3% in weight) and traces of decorin (Choudhury et al, 2006). Washing with PBS removes inorganic salts that are normally present in pickled skin, which might be harmful for cell cultures.…”
Section: Discussionmentioning
confidence: 97%
“…Table 3 shows the main proteins identified in different collagen-based substrates. Proteomics analysis of leather indicates that de-hairing and tanning treatments not only removes the keratins from hair and the epidermis but also minor proteins such as proteoglycans and elastin [66]. In archaeological leather, mainly collagen has been detected [9].…”
Section: Conservar Património 31 (2019) 106mentioning
confidence: 99%
“…In fact, numerous examples may be found in the literature, on that same variety of tissues and products. They include muscle [1,2], meat products and their transformation [3], liver and related products [4], milk and dairy products [5], eggs [6,7], honeybee products [8], animal fibers like wool, cashmere or mohair [9], hides [10], reproductive organs and reproduction-related fluids [11], such as sperm or blood-based fluids, namely serum or plasma [12]. The afore-mentioned complexity is further increased if farm animal proteomics, includes an increasing number of disease and parasitosis causing agents, such as bacteria, viruses and protozoa, as well as possible vectors of such diseases namely ticks, flies and mosquitoes.…”
Section: Farm Animal Proteomicsmentioning
confidence: 99%
“…In earlier studies, the bulk of proteomic work seems to rely on PMF, a strategy used for instance in horse serum [117], cattle mammary gland [118] and adipocytes [119], lambskin leather [10] and ovine liver [120]. Although gradually losing importance, PMF is still used in recent studies such as those by Sun et al [121] on the proteomic mechanisms of infection of pigs with Swine fever virus.…”
mentioning
confidence: 95%